Perbandingan Motivasi Belajar Siswa Menggunakan Produk Pengembangan Bahan Ajar Bentuk Surat Kabar dengan Lembar Kerja Siswa (LKS) - Silvi Apipatus Saadah (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2020)
The purpose of this development research is to describe the product development of mathematics teaching materials in the form of newspapers and to compare the learning motivation of students using newspaper-form teaching materials with students using Student Worksheets (LKS). The method used is the type of Research and Development (R & D) research with the ADDIE development model which stands for Analysis, Design, Development, Implementation, Evalution and at the field trial stage the researchers used a real experimental design in this design, there are two groups namely one group obtained experimental treatment. Both groups were given post-test but were not given pre-test. The data analysis technique used is the Independent T Test. Based on the results of the study, this teaching material product is feasible to be used as teaching material in the classroom as evidenced by the results of the validation of experts. In the material validation, the percentage of eligibility reached 90.5% and the percentage of eligibility for design expert validation reached 95.83% and the percentage of eligibility obtained from student responses reached 86.77%. The percentage of achievement of the three is in the proper classification for use in learning. For students' learning motivation the experimental class obtained an average of 124.68 while the learning motivation of control class students gained an average of 116.04. The t-test calculation results from the average learning motivation of the experimental and control classes, Sig. (2-tailed) produces a number of 0.001. The results of the Sig. (2-tailed) <0.05. This shows that H0 is rejected and H1 is accepted, meaning that there is a significant difference between the experiment class motivation and control. Motivation of student learning by using teaching materials in the form of newspapers in learning is better than students' learning motivation using teaching materials student worksheets (LKS).